Didactic Design of Mathematics: Recognizing Flat Shapes Using Traditional Cakes (Onde-Onde, Lemper, Kue Lapis) - Putri Rahmadani; Risnawati; M. Fikri Hamdani (Global Action and Education for Society, 2026)
This study aims to design and analyze a didactical design in mathematics for introducing plane shapes to elementary school students using traditional cakes as learning media, namely onde-onde, lemper, and kue lapis. The method employed is Didactical Design Research (DDR), which consists of three stages: initial didactical situation analysis, metapedadidactical analysis, and retrospective analysis. Through observation and interviews, it was found that concrete media based on local culture can enhance students’ understanding of geometric shape concepts. The didactical interaction between teacher, students, and learning materials became more active and meaningful. This design demonstrates that a contextual approach is not only effective in delivering mathematical content, but also supports cultural preservation and strengthens students’ learning motivation.